Clinicopathological and demographical characteristics of non-small cell lung cancer patients with ALK rearrangements: a systematic review and meta-analysis. - Liang Fan; Yun Feng; Huanying Wan; Guochao Shi; Wenquan Niu (PLoS ONE)
Objective This meta-analysis aimed to comprehensively examine the relationship between the clinicopathological and demographical characteristics and ALK rearrangements in patients with non-small cell lung cancer (NSCLC). Methods and main findings In total, 62 qualified articles including 1178 ALK rearranged cases from 20541 NSCLC patients were analyzed, and the data were extracted independently by two investigators. NSCLC patients with ALK rearrangements tended to be younger than those without (mean difference: -7.16 years; 95% confidence interval (95% CI): -9.35 to -4.96; P<0.00001), even across subgroups by race. Compared with female NSCLC patients, the odds ratio (OR) of carrying ALK rearrangements was reduced by 28% (95% CI: 0.58-0.90; P = 0.004) in males, and this reduction was potentiated in Asians, yet in opposite direction in Caucasians. Likewise, smokers were less likely to have ALK rearrangements than never-smokers (OR = 0.33; 95% CI: 0.25-0.44; P<0.00001), even in race-stratified subgroups. Moreover, compared with NSCLC patients with tumor stage IV, ALK rearrangements were underrepresented in those with tumor stage I-III (OR = 0.58; 95% CI: 0.44-0.78; P = 0.0002). Patients with lung adenocarcinomas had a significantly higher rate of ALK rearrangements (7.2%) than patients with non-adenocarcinoma (2.0%) (OR = 2.25; 95% CI: 1.54-3.27; P<0.0001). Conclusion Our findings demonstrate that ALK rearrangements tended to be present in NSCLC patients with no smoking habit, younger age and tumor stage IV. Moreover, race, age, gender, smoking status, tumor stage and histology might be potential sources of heterogeneity.